2010
DOI: 10.1097/brs.0b013e3181cc3f56
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Lumbar Disc Herniation With Associated Radiculopathy

Abstract: Advice is less effective than microdiscectomy in the short term but equally effective in the long term for people who have LDHR. Moderate evidence favors stabilization exercises over no treatment, manipulation over sham manipulation, and the addition of mechanical traction to medication and electrotherapy. There was no difference among traction, laser, and ultrasound. Adverse events were associated with traction and ibuprofen. Additional high-quality trials would allow firmer conclusions regarding adverse effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
1
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 81 publications
1
109
1
6
Order By: Relevance
“…Our study will explore the frequency of usage of these technique systems in particular musculoskeletal conditions. With regards to the specific conditions we surveyed there is only limited positive evidence available in the literature for manipulative treatment (in isolation or as part of the therapy) of cervicogenic headache [15], myofascial pain syndrome [10], cervical radiculopathy [16], lumbar disc syndrome [2], lumbar stenosis [17], lumbar disc herniation [18,19] and sacroiliac dysfunction [20]. However, the evidence is weak due to lack of randomised controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Our study will explore the frequency of usage of these technique systems in particular musculoskeletal conditions. With regards to the specific conditions we surveyed there is only limited positive evidence available in the literature for manipulative treatment (in isolation or as part of the therapy) of cervicogenic headache [15], myofascial pain syndrome [10], cervical radiculopathy [16], lumbar disc syndrome [2], lumbar stenosis [17], lumbar disc herniation [18,19] and sacroiliac dysfunction [20]. However, the evidence is weak due to lack of randomised controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of the cases radiculopathy are caused by a herniation of the lumbar intervertebral disc, making it the most common cause 25,26) . The highest prevalence is seen in the 30-to 50-year-old age group.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…This is particularly interesting as disk cells are of notochordal in origin [15], and do not contain either sensory or motor neurons under physiological conditions [16]. Recently, Cuesta et al [17] showed the presence and localization of different ASICs in the human healthy intervertebral disk, and an increased expression of ASICs in the degenerated intervertebral disk, indicating that ASICs may be involved in intervertebral disk degeneration.…”
Section: Discussionmentioning
confidence: 99%